Expecting the Worst: Exploring the Associations Between Poverty and Misbehavior. - Smith, Laura; Allen, Alizah; Bowen, Rashidah (Journal of Poverty)
What associations exist between class membership and perceptions of misbehavior? Participants received a list of 174 infractions and crimes, and were asked with which social class category (poor, working class, middle class, or wealthy) they most associated each. Results indicated that (a) most infractions were considered equally likely to be committed by any social class, (b) respondents linked class categories with infractions that referred to particular social class experiences, (c) the Poor/Low-Income category was the only one associated with infractions that did not contain class references, and (d) respondents did not associate middle-class membership most highly with any infractions.